Students’ Perception of Implementation of Online Learning and Face-to-face Learning - Ulfa Kurnia Citra; Baso Jabu; Geminastiti Sakkir (Journal of Excellence in English Language Education, 2023)
The purpose of this study was to investigate how English education students perceived their English proficiency both during online and in-person learning. The study was carried out in the Department of Languages and Literature, with a focus on English education. Students in the class 2020 for English language instruction made up the population in this study. Interviews and documents served as the research's primary data sources. Based on the study's findings, the researcher concluded that face-to-face instruction is the best method for teaching students how to use their English more effectively.